Regulatory roles of circRNAs in adipogenesis and lipid metabolism: emerging insights into lipid‐related diseases. (3rd September 2020) - Chen, Chen; Zhang, Xing; Deng, Yuan; Cui, Qingming; Zhu, Ji; Ren, Huibo; Liu, Yingying; Hu, Xionggui; Zuo, Jianbo; Peng, Yinglin
Abstract : Disorder of lipid metabolism has become an urgent health problem that brings about a variety of metabolic syndromes, including hepatic steatosis, adipose tissue dysfunction, diabetes and obesity. Circular RNAs (circRNAs), a class of emerging RNA molecules with unique structure and extensive effects, have been verified to participate in various biological programs through distinct mechanisms, especially in lipid‐related processes. In this review, the biogenesis, characteristics, and functional mechanisms of circRNAs are discussed. Furthermore, the methods for circRNA identification and expression profiles of circRNAs associated with adipogenesis and lipid metabolism are described. Additionally, we emphasize the regulatory roles of circRNAs in adipogenesis, lipid metabolism, and lipid‐related diseases. Finally, the diagnostic and therapeutic potential of circRNAs is highlighted, showing potential for the clinical application of circRNAs in the treatment of lipid‐related diseases in the near future. Abstract : The biogenesis, characteristics, and functional mechanisms of circRNAs are introduced. Then, the methods for circRNA identification and expression profiles of circRNAs associated with adipogenesis and lipid metabolism are summarized. In particular, investigations on the emerging role of circRNAs in regulating adipogenesis and lipid metabolism are reviewed, indicating that circRNAs could be exploited as potential biomarkers for developing powerfully therapeutic strategies against lipid‐related diseases.